Antioxidant Effectiveness Test on The Formulation of Combination Facial Soap Ingredients of Ethanol Extract Lemon Peel Citrus limon and Forest Honey Apis dorsata - Sriyanty Sadsyam; Nasrawati Basir; Arafah Nurfadillah; Nurhikmah Awaluddin; Selviana (Nusantara Scientific Medical, 2023)
Citrus limon and Apis dorsata are claimed to have several active compounds namely: alkaloids, flavonoids, tannins and saponins. These compounds are known to have antioxidant activity in preventing skin damage due to free radicals and preventing premature aging. In this study, Citrus limon and Apis dorsata were formulated into facial soap ingredients. The purpose of this study was to find out whether the ethanol extract formulation in the lemon peel and the Apis dorsata forest honey has the effectiveness of antioxidants in preventing the free radicals. This research was an experimental study with physical and chemical evaluation of ingredients. The DPPH test was used to determine the antioxidant activity of the ingredients. This research used three types of formulation of Ethanol Ethanol Extract Formulation were lemon and honey forest, they were : FI (5%: 2%); FII (5%: 3%) and FIII (5%: 4%). The results of the DPPH test respectively were FI 6,16; FII 5,53 and FIII 4.39. The ingredients of Facial Soap Combination of Ethanol Extract Lemon Feel and Apis dorsata had the best antioxidant and antioxidant energy in Formula III with concentration of 5%: 4%